Empowering a Young Mother Through Continuity of Care: A Case Report of a Primiparous Woman's Journey - Zahra Amalia; Rabia Wahdah; Nita Hestiyana; Winda Maolinda (Open Access Indonesian Journal of Medical Reviews, 2024)
Continuity of midwifery care (CoMC) is a model of care in which a woman is supported by the same midwife, or a small team of midwives, throughout her pregnancy, childbirth, and the postpartum period. This model has been shown to have several benefits for women and their babies, including reduced rates of intervention, increased satisfaction with care, and improved maternal and neonatal outcomes. This case report describes the experiences of a 21-year-old primiparous woman who received CoMC from a midwife in a community setting. The woman was highly satisfied with the care she received, reporting that she felt empowered and in control of her pregnancy and childbirth experience. She also felt that the midwife was a trusted source of support throughout her journey. In conclusion, this case report provides further evidence of the benefits of CoMC for women and their babies, particularly for young mothers who may require additional support and guidance. It highlights the importance of providing woman-centered care that is responsive to the individual needs of each woman.